2020
DOI: 10.3390/cells9092041
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils and Neutrophils—Molecular Differences Revealed by Spontaneous Raman, CARS and Fluorescence Microscopy

Abstract: Leukocytes are a part of the immune system that plays an important role in the host’s defense against viral, bacterial, and fungal infections. Among the human leukocytes, two granulocytes, neutrophils (Ne) and eosinophils (EOS) play an important role in the innate immune system. For that purpose, eosinophils and neutrophils contain specific granules containing protoporphyrin-type proteins such as eosinophil peroxidase (EPO) and myeloperoxidase (MPO), respectively, which contribute directly to their anti-infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
6
10
0
1
Order By: Relevance
“…The existence of a huge number of immature cells in HUCB has also been reported [ 6 ]. In this study, granulocytes, including band cells, basophils, eosinophils, and neutrophils, showed ultrastructural characteristics similar to those in humans, as described by some authors [ 7 - 10 ]. Human and UCB cells have similar structures, suggesting that bovine umbilical cords could constitute a model for human umbilical cord research and medication-based therapy for stem cell and cell-free therapy.…”
Section: The Structure Of Bovine Umbilical Cordssupporting
confidence: 87%
“…The existence of a huge number of immature cells in HUCB has also been reported [ 6 ]. In this study, granulocytes, including band cells, basophils, eosinophils, and neutrophils, showed ultrastructural characteristics similar to those in humans, as described by some authors [ 7 - 10 ]. Human and UCB cells have similar structures, suggesting that bovine umbilical cords could constitute a model for human umbilical cord research and medication-based therapy for stem cell and cell-free therapy.…”
Section: The Structure Of Bovine Umbilical Cordssupporting
confidence: 87%
“…Commonly, eosinophils are a kind of white blood cells, measuring 10-20 µm in diameter, with a bilobed nucleus [4] (Figures 1 and 2). In homeostatic situations, they circulate in the bloodstream ranging from 0 to 500 eosinophils per microliter [5].…”
Section: Unraveling the Complex Biology Of Eosinophils: From Development To Trafficmentioning
confidence: 99%
“…Further studies combining fluorescence tags and RS include bladder cancer cells expressing the widely used GFP to monitor the distribution of proteins in living cells 74 and the investigation of biochemical features of immune cells eosinophils and neutrophils. 75 In addition to the here reviewed spontaneous RS, FS has also been combined in several studies with surface-enhanced Raman scattering using nanoparticles to enhance the singal. 76 79 …”
Section: Optical Modalities For Medical Diagnosticsmentioning
confidence: 99%